2021
DOI: 10.1039/d1ra01064f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability as a quality attribute for the cell therapy raw material human serum albumin

Abstract: An overall attribute for the consistency in pharmaceutical quality of human serum albumin encompasses a global measure of conformational stability, as measured by CD, DLS, QCM-D or LSPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…[108] Whereas recombinant HSA containing octanoate stabilizer disclosed maximum solution-phase conformational stability and minimum adsorption-related deformation among all tested albumin samples. [109] By contrast, adsorption studies demonstrate least conformational stability was observed by BSA derived from plasma compared to other tested samples and underwent colloidal stability and conformational changes upon exposure to external stresses such as solid-liquid interfaces and high temperature. [108,109] For drug binding and conjugation, HSA shows superiority owing to the hollow cavity of subdomain II.…”
Section: Hsa Bsamentioning
confidence: 93%
See 1 more Smart Citation
“…[108] Whereas recombinant HSA containing octanoate stabilizer disclosed maximum solution-phase conformational stability and minimum adsorption-related deformation among all tested albumin samples. [109] By contrast, adsorption studies demonstrate least conformational stability was observed by BSA derived from plasma compared to other tested samples and underwent colloidal stability and conformational changes upon exposure to external stresses such as solid-liquid interfaces and high temperature. [108,109] For drug binding and conjugation, HSA shows superiority owing to the hollow cavity of subdomain II.…”
Section: Hsa Bsamentioning
confidence: 93%
“…[109] By contrast, adsorption studies demonstrate least conformational stability was observed by BSA derived from plasma compared to other tested samples and underwent colloidal stability and conformational changes upon exposure to external stresses such as solid-liquid interfaces and high temperature. [108,109] For drug binding and conjugation, HSA shows superiority owing to the hollow cavity of subdomain II. [110] BSA employed Leu-237 residue on subdomain IIA directed toward the least carrying capability.…”
Section: Hsa Bsamentioning
confidence: 93%
“…This means that HSA molecules are more prone to aggregating or sticking together in solution, which can lead to a loss in stability and an increase in solution viscosity. On the other hand, BSA has higher colloidal stability, meaning that its molecules are more resistant to aggregation and precipitation, resulting in a more stable and uniform solution structure [54]. Overall, the difference in stiffness between the HSA and BSA solutions could be attributed to their structural differences and resulting differences in binding forces, as well as their conformational and colloidal stabilities.…”
Section: Brillouin Scattering Of Bsa and Hsa Solutionsmentioning
confidence: 99%
“…Human serum albumin (HSA) is a principal extracellular protein with a concentration of 40 mg•mL −1 or 0.6 mM in blood plasma and contains 50-60% of total plasma protein in humans [7,8]. Research showed that the distribution, free concentration, and metabolism of drugs can be considerably altered as a result of their binding to HSA [9][10][11]. If the affinity of the drug binding to HSA in the plasma is strong, the drug will be transported to the target tissue and cannot be dissociated from HSA.…”
Section: Introductionmentioning
confidence: 99%